ASSESSING THE MEDIATION ROLE OF BRAND ATTACHMENT: AN EMPIRICAL STUDY AMONG TOURISTS IN MALAYSIA - Rosli, Nadzirah; Che-Ha, Norbani; M. Ghazali, Ezlika (Journal of Human Capital Development (JHCD), 2021)
Abstract. The purpose of this article is to explore the relationship of hotel attributes on consumers’ satisfaction and revisit intention through mediation of brand attachment. The stimulus-organism-response (SOR) theory is utilized in the study to examine the relationships between the constructs. To validate the research model and hypotheses, the study used a partial least squares structural equation modelling (PLS-SEM) approach. The empirical evidence was collected from 474 Malaysian tourist. The results showed that brand attachment mediates the relationship between hotel attributes and satisfaction as well as revisit intention. In addition, the indirect effect of hotel attributes on revisit intention through brand attachment and satisfaction sequentially are also supported. This paper attempt to offers new insights into how brand attachment influences the relationship between hotel attributes and satisfaction as well as revisit intention. This study determined that hotels should consider the importance of brand such as brand attachment in developing sustainable marketing tactics. These findings might support practitioners and decision makers to focus on brand related functions that could be utilized to achieve competitive advantage. Keywords: Hotel attributes, brand attachment, satisfaction, revisit intention, branding, Malaysia